1997
DOI: 10.1046/j.1365-2249.1997.d01-948.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of beta2-glycoprotein I and anticardiolipin antibodies in oxidatively modified low-density lipoprotein uptake by macrophages

Abstract: Anticardiolipin antibodies (aCL) in the sera of patients with antiphospholipid syndrome (APS) recognize an altered structure of beta 2-glycoprotein I (beta 2-GPI) interacting with solid-phase negatively charged phospholipids. beta 2-GPI bound to Cu2+-oxidized plasma lipoproteins, i.e. oxidized very low-density lipoprotein (oxVLDL), oxidized low-density lipoprotein (oxLDL), or oxidized high-density lipoprotein (oxHDL). beta 2-GPI inhibited in vitro uptake, i.e. cell surface binding, cellular association, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
101
0
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(113 citation statements)
references
References 35 publications
8
101
0
4
Order By: Relevance
“…oxLDL has been implicated in the pathogenesis of atherosclerosis [5]and previous studies suggested that immune mechanisms are involved in atherogenesis [41]. We previously demonstrated that oxLDL formed complexes with β 2 GPI, which were subsequently targeted by anti-β 2 GPI autoantibodies, considered the pathogenic autoantibodies in patients with APS [21, 22, 23, 24]. Based on these findings, we established a sandwich ELISA for detecting oxLDL/β 2 GPI complexes in serum samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…oxLDL has been implicated in the pathogenesis of atherosclerosis [5]and previous studies suggested that immune mechanisms are involved in atherogenesis [41]. We previously demonstrated that oxLDL formed complexes with β 2 GPI, which were subsequently targeted by anti-β 2 GPI autoantibodies, considered the pathogenic autoantibodies in patients with APS [21, 22, 23, 24]. Based on these findings, we established a sandwich ELISA for detecting oxLDL/β 2 GPI complexes in serum samples.…”
Section: Discussionmentioning
confidence: 99%
“…It is now widely understood that the major autoantigen for anticardiolipin antibodies found in the sera of APS patients is β 2 -glycoprotein I (β 2 GPI) [16, 17, 18, 19, 20]. It has also been shown that β 2 GPI specifically binds to Cu 2+ -oxLDL, not to other chemically modified LDLs, and that anti-β 2 GPI autoantibodies bind to oxLDL/β 2 GPI complexes [21, 22, 23, 24]. Based on these findings, we established a novel sandwich ELISA system for the detection of serum oxLDL/β 2 GPI complexes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that aPL antibodies, in particular anti-␤2GPI antibodies, can accelerate the influx of ox-LDLs into macrophages. 14 Other autoantibodies, such as anti-high-density lipoproteins (HDLs) and antiapolipoprotein A-I, also have been detected in APS. In addition, macrophages and ECs bind to ␤2GPI during the atherosclerotic process.…”
Section: Introductionmentioning
confidence: 99%
“…A role for ␤ 2 GPI as a naturally occurring anticoagulant is suggested by reports that it inhibits the prothrombinase (12) and Factor X activating complexes (13), although the physiologic importance of these effects is uncertain. ␤ 2 GPI may also promote the clearance of senescent cells (14,15) and regulate the uptake of lipoproteins by macrophages (16).…”
mentioning
confidence: 99%